Detailed examination of the influence of surfactants on the thermal reliability of molten salt microcapsules for high-temperature latent heat storage - Ji, Yun Hwan; Jo, Byeongnam (Journal of Molecular Liquids, 2025)
The thermal reliability of encapsulated phase change materials is important for maintaining the storage density of latent heat storage (LHS) systems under repeated charging and discharging processes. Therefore, this study investigated the influence of polyvinylpyrrolidone (PVP), a surfactant, on the thermal reliability of microencapsulated potassium nitrate (KNO3) in a silica (SiO2) shell in repeated heating and cooling cycles. Different amounts of the surfactant were employed in a sol–gel reaction-based microencapsulation process. The thermal reliability of the microcapsules was examined by comparing their thermal properties, such as the melting peak temperature and melting enthalpy, during 50 repeated heating and cooling cycles using differential scanning calorimetry. In the thermal reliability tests, the thermal properties of the surfactant-aided KNO3 microcapsules drastically changed during the thermal cycle, whereas those of the surfactant-free KNO3 microcapsules remained consistent. Moreover, the melting curves of the surfactant-aided microcapsules exhibited remarkable variations. In addition, the mass loss of the microcapsules for prolonged heating at 400 °C was proportional to the amount of the surfactant used in the encapsulation process, which was attributed to the thermal decomposition of PVP based on thermogravimetric analysis. Using a surfactant deteriorates the thermal reliability of KNO3@SiO2 microcapsules. Furthermore, the superior thermal performance and outstanding thermal reliability of surfactant-free KNO3@SiO2 microcapsules compared to those of surfactant-aided KNO3@SiO2 microcapsules are beneficial for LHS systems.
Keywords: Heating and cooling cycles; High temperature thermal energy storages; Latent heat storage system; Microcapsules; Molten salt; Polyvinylpyrrolidones; Property; SiO 2; Thermal; Thermal reliability; High-temperature thermal energy storage; Microencapsulation; Molten salt; Surfactant; Thermal reliability